2006
DOI: 10.1128/mcb.26.8.3327-3334.2006
|View full text |Cite
|
Sign up to set email alerts
|

Replication Fork Progression Is Impaired by Transcription in Hyperrecombinant Yeast Cells Lacking a Functional THO Complex

Abstract: THO/TREX is a conserved, eukaryotic protein complex operating at the interface between transcription and messenger ribonucleoprotein (mRNP) metabolism. THO mutations impair transcription and lead to increased transcription-associated recombination (TAR). These phenotypes are dependent on the nascent mRNA; however, the molecular mechanism by which impaired mRNP biogenesis triggers recombination in THO/TREX mutants is unknown. In this study, we provide evidence that deficient mRNP biogenesis causes slowdown or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
121
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 48 publications
14
121
0
Order By: Relevance
“…We have recently shown that transcription impairment of hpr1⌬ along a highly transcribed lacZ gene causes a retardation of replication, observed as a slowdown of fork progression (43). This slowdown of fork progression could partially be suppressed by ribozyme-mediated cleavage of the mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that transcription impairment of hpr1⌬ along a highly transcribed lacZ gene causes a retardation of replication, observed as a slowdown of fork progression (43). This slowdown of fork progression could partially be suppressed by ribozyme-mediated cleavage of the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…All data were normalized with respect to the endogenous U3 signal. (43). While S-phase-specific transcription was capable of inducing recombination, G 2 -specific transcription was not.…”
Section: Nuclear Accumulation Of Poly(a)mentioning
confidence: 99%
“…TREX subunits have been shown to be important for maintenance of the genomic stability of transcribed sequences (31). Recent work indicates that mutants in the TREX subunit called Hpr1 lead to disrupted transcription and mRNP biogenesis that inhibit the movement of replication forks through areas of the genome undergoing transcription during S phase (42). As Yra1 is a member of the TREX complex, it is possible that yra1 mutants could also lead to defective mRNP biogenesis that disrupts DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Although recombination is also enhanced by transcription, the mechanisms underlying transcription-associated recombination may be different from those of TAM. Thus, impairment of replication progression by transcription may be a critical factor triggering transcriptionassociated recombination (43,44), but this is not obvious for TAM. Our study reveals that THO mutations lead to a low hypermutator phenotype in the LAUR system, which is based on a highly expressed lacZ gene (Fig.…”
Section: Discussionmentioning
confidence: 99%